‘Asi: Working with the Unseen Spirit - Faumuina, Cecelia; Mortensen Steagall, Marcos (Communication Design Department, School of Art and Design, Auckland University of Technology, 2023)
In 1993, Wolfgramm referred to the climax in faiva (Tongan artistic performance)1 as ‘asi (the presence of the unseen). This spirit of artistic expression is an agent sometimes identified when Oceanic people work together to bring artistic projects to their apotheosis. Building on the idea of the unseen spirit that energises and gives agency to artistic work, this article discusses occurrences that surface when young Oceanic people collaborate artistically, drawing on values from their cultural heritage to create meaningful faiva. Emanating from my 2022 PhD study ‘Asi - The Presence of the Unseen, the article considers how, in a group of New Zealand secondary school students aged between 10 and 18, ‘asi brought forward a powerful spirit of belonging that resourced their artistic practice. The research proposed that the ‘asi identifiable at the peak of an artistic performance, might also be discernible before and after such an event, and resource the energy of artistic practice as a whole. The research considered a co-created project called Lila. This was developed by a team of students who combined talents and experiences to produce a contemporary faiva for presentation in 2019. In understanding ‘asi the project drew on student reflections, the researchers experience and interviews with contemporary Oceanic youth leaders who discussed the nature and agency of ‘asi as a phenomenon that might resource artistic practice. The significance of the research project lay in its contribution to a distinctive understanding of ‘asi, such that we might identify and consider its potential agency for resourcing creativity and belonging inside the development and performance of contemporary artistic practices among Oceanic youth.